P90 Vitamin D status improves following recovery from tuberculosis. (14th November 2013) - Witt, KD; Jolliffe, DA; Wang, Z; Thummel, KE; Timms, PM; Griffiths, CJ; Martineau, AR
Abstract : Introduction and Objectives: Vitamin D deficiency associates with active tuberculosis, but the question of whether this arises as a cause or as a consequence of disease is controversial. Paired comparison of vitamin D status of TB patients at diagnosis and following recovery has potential to inform the debate, but such studies have not previously been conducted. Methods: We conducted a longitudinal study comparing serum concentrations of vitamin D metabolites in TB patients at long-term follow-up vs. diagnosis. Participants diagnosed with pulmonary TB in 2007–9 were invited to attend a follow-up visit in 2012. Concentrations of 25-hydroxyvitamin D (25[OH]D, the measure of vitamin D status), 1α, 25-dihydroxyvitamin D (1, 25[OH]2 D), 24R, 25-dihydroxyvitamin D (24, 25(OH)2 D), 4β, 25-dihydroxyvitamin D (4, 25[OH]2 D), calcium, albumin, parathyroid hormone (PTH) and vitamin D binding protein (DBP) were determined in serum samples collected at follow-up and at the time of TB diagnosis. Values at the two time points were compared using Student's paired t-tests. Results: Thirty-one participants were followed up between August 2012 and February 2013. Serum 25(OH)D concentrations were significantly higher post-recovery than at diagnosis (mean 29.7 vs. 12.2 nmol/L, p < 0.0001). Participants also had higher mean serum concentrations of PTH, corrected calcium and 24, 25(OH)2 D post-recovery than at diagnosis (PTH, 4.97 vs. 2.78 pmol/L, p = 0.0003; corrected calcium, 2.50 vs. 2.45 mmol/L, p = 0.03; 24, 25(OH)2 D, 3.15 vs. 1.53 nmol/L, p = 0.004). No statistically significant differences in serum concentrations of 1, 25(OH)2 D, 4, 25(OH)2 D or DBP were seen between the two time points. Differences in serum concentrations of 25(OH)D at follow-up vs. baseline remained statistically significant after exclusion of 14 participants who were taking supplemental vitamin D at follow-up and / or who had increased their sun exposure since time of diagnosis (p = 0.005), and after exclusion of 17 participants whose baseline sample was taken from March to July inclusive (p = 0.0003). Conclusions: Vitamin D status of TB patients improved after resolution of tuberculosis. This phenomenon was not explained by differences in vitamin D supplementation, self-reported sun exposure or season of sampling at follow-up vs. baseline. Our findings raise the possibility that vitamin D deficiency may be a consequence, as well as a cause, of active tuberculosis.